The First Legislative Regulations on Civil Veterinary Medicine in the Ottoman State - Melikoǧlu Gölcü, B. (Chartered Inst. of Building Services Engineers hq@cibse.org, 2015)
In Turkey, civil veterinary education was started in 1871 at the Military Academy and continued with the foundation of the first Civil Veterinary School in 1889. As from the last quarter of the nineteenth century, various legal arrangements were made to regulate the veterinary services conducted for the civil population. Through the enforcement of the first legal arrangements on the employment of civil veterinarians in Turkey, a major step was taken in the development of the veterinary profession and the fight against contagious animal diseases in the country. This study is aimed at assessing the legal arrangements made for the delivery of civil veterinary services in the Ottoman State, in light of newly acquired information, and thus, at contributing to the history of veterinary medicine. © Chartered Inst. of Building Services Engineers. All Rights Reserved.
Osmanlı Devleti’nde Sivil Veteriner Hekimliğine Yönelik İlk Mevzuat Düzenlemeleri
Keywords: Civil Veterinary Medicine; History; Legislation